Development of PBL with Interactive PowerPoint and Quizizz to Improve Elementary Students’ Understanding and Confidence - Melinda Insania Rahayu Melin; Anik Yuliani; Luvy Sylviana Zanthy (Jurnal Elementaria Edukasia, 2026)
The development of a problem-based learning model is urgent so that learning can be better tailored to children’s characteristics, with the hope that children will gain good conceptual and affective understanding. Teachers still face several challenges when applying the PBL model. The purpose of this study is to examine the development process and feasibility of a problem-based learning model assisted by interactive PowerPoint and Quizizz to enhance students’ conceptual understanding of IPAS and their self-confidence, as well as to assess the effectiveness of this model and these media in improving students’ understanding and self-confidence in IPAS lessons. This study utilized the R&D method. The research subjects were third-grade elementary school students in three different classes for the pilot test. Data were collected through observation, tests, questionnaires, and document analysis. The data were analyzed using Excel for the validation of observation results and questionnaires, SPSS for test questions and questionnaires, and Miles & Huberman for observational data. The research results showed that the average score on the validation test of the teaching materials was categorized as very good. Regarding the test results on conceptual understanding, there was an increase from an average of 72.81 before the intervention to 83.53 afterward. The average score for students’ self-confidence was 68.00 before the intervention and increased to 85.61 afterward. During the dissemination session, the researchers shared their findings with fellow teachers and recommended the use of the developed model and media in instruction, citing several benefits and noting that the approach aligns with the characteristics of elementary school students; it appears that teachers are eager to try applying it. Keywords: PBL Development; Interactive PowerPoint; Quizizz; Conceptual Understanding; Self-Confidence